NMDA Receptor Subunits in the Adult Rat Hippocampus Undergo Similar Changes after 5 Minutes in an Open Field and after LTP Induction - Baez, Maria Veronica (2013)
NMDA receptor subunits change during development and their synaptic expression is modified rapidly after synaptic plasticity induction in hippocampal slices. However, there is scarce information on subunits expression after synaptic plasticity induction or memory acquisition, particularly in adults. GluN1, GluN2A and GluN2B NMDA receptor subunits were assessed by western blot in 1) adult rats that had explored an open field (OF) for 5 minutes, a time sufficient to induce habituation, 2) mature rat hippocampal neuron cultures depolarized by KCl and 3) hippocampal slices from adult rats where long term potentiation (LTP) was induced by theta-burst stimulation (TBS). GluN1 and GluN2A, though not GluN2B, were significantly higher 70 minutes ?but not 30 minutes- after a 5 minutes session in an OF. GluN1 and GluN2A total immunofluorescence and puncta in neurites increased in cultures, as evaluated 70 minutes after KCl stimulation. Similar changes were found in hippocampal slices 70 minutes after LTP induction. To start to explore underlying mechanisms, hippocampal slices were treated either with cycloheximide (a translation inhibitor) or actinomycin D (a transcription inhibitor) during electrophysiological assays. It was corroborated that translation was necessary for LTP induction and expression. The rise in GluN1 depends on transcription and translation, while the increase in GluN2A appears to mainly depend on translation, though a contribution of some remaining transcriptional activity during actinomycin D treatment could not be rouled out. LTP effective induction was required for the subunits to increase. Although in the three models same subunits suffered modifications in the same direction, within an apparently similar temporal course, further investigation is required to reveal if they are related processes and to find out whether they are causally related with synaptic plasticity, learning and memory.